Improving Mental Health Service Utilization Among Men: A Systematic Review and Synthesis of Behavior Change Techniques Within Interventions Targeting Help-Seeking. Issue 3 (June 2019) - Sagar-Ouriaghli, Ilyas; Godfrey, Emma; Bridge, Livia; Meade, Laura; Brown, June S.L.
Compared to women, men are less likely to seek help for mental health difficulties. Despite considerable interest, a paucity in evidence-based solutions remains to solve this problem. The current review sought to synthesize the specific techniques within male-specific interventions that may contribute to an improvement in psychological help-seeking (attitudes, intentions, or behaviors). A systematic review identified 6, 598 potential articles from three databases (MEDLINE, EMBASE, and PsycINFO). Nine studies were eligible. A meta-analysis was problematic due to disparate interventions, outcomes, and populations. The decision to use an innovative approach that adopted the Behavior Change Technique (BCT) taxonomy to synthesize each intervention's key features likely to be responsible for improving help-seeking was made. Of the nine studies, four were engagement strategies (i.e., brochures/documentaries), two randomized controlled trials (RCTs), two pilot RCTs, and one retrospective review. Regarding quality assessment, three were scored as "strong, " five as "moderate, " and one as "weak." Key processes that improved help-seeking attitudes, intentions, or behaviors for men included using role models to convey information, psychoeducational material to improve mental health knowledge, assistance with recognizing and managing symptoms, active problem-solving tasks, motivating behavior change, signposting services, and, finally, content that built on positive male traits (e.g., responsibility and strength). This is the first review to use this novel approach of using BCTs to summarize and identify specific techniques that may contribute to an improvement in male help-seeking interventions, whether engagement with treatment or the intervention itself. Overall, this review summarizes previous male help-seeking interventions, informing future research/clinical developments.